PENGARUH PERERANGKAAN PESAN PADA PERSEPSI RISIKO KONSUMEN DENGAN MOTIVASI SEBAGAI VARIABEL PEMODERASI* - Euis, Soliha; BM., Purwanto (Proceeding Fakultas Ekonomi, 2012)
This study examines the effect of message framing on consumer risk perception moderated byconsumer motivation. Between groups, 2x2 factorial design is employed to test the hypotheses. Messageframing is the independent variable and is manipulated into positive and negative message framing.Consumer motivation and consumer risk perception are measured variables. Consumer motivation is amoderating variable and categorized into rational and emotional motivation. The results of the studyshow that: (1) there is significant difference in consumer risk perception between that with positivemessage framing and that with negative message framing and (2) consumer motivation moderate theeffect of message framing on consumer risk perception.Keywords: message framing, motivation, rational motives, emotional motives, consumer risk perception